Pengaruh Budaya Organisasi Dan Motivasi Kerja Terhadap Produktivitas Karyawan PT Bisma Aero Sejahtera Kota Tangerang: The Influence of Organizational Culture and Work Motivation on Employee Productivity of PT Bisma Aero Sejahtera Tangerang City - Zidan Ramadani Saputra; Ratih Hastasari; Wawan Saputra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
A strong organizational culture is believed to create a conducive work environment, while high work motivation can encourage employees to work more optimally, thereby increasing employee productivity in the workplace. This research aims to investigate the role of Organizational Culture and Work Motivation in enhancing employee productivity at PT Bisma Aero Sejahtera.Using a sample of 70, the study employed analysis techniques such as validity tests, reliability tests, classical assumption tests, regression analysis, and hypothesis testing through T-tests and F-tests.Based on the research findings, partially, the x1 organizational culture variable did not significantly affect employee productivity. However, the x2 work motivation variable partially and significantly influenced employee productivity. Simultaneously, both variables (organizational culture and work motivation) had a significant impact on the productivity of PT BAS employees. Keywords: Organizational Culture, Work Motivation, Employee Productivity